Using Confocal Laser Scanning Microscopy (CLSM) for diagnosis of Terebrantia (Thysanoptera) - Matthias Becker; Gritta Schrader; Björn Hoppe; Frederik Stein; Christine Pokoj; Stephanie Feltgen (Journal für Kulturpflanzen)
Thrips, insects from the order Thysanoptera, are often intercepted in consignments sent from third countries into the European Union. Rapid species identification is needed in order to quickly decide, whether phytosanitary measures are required or a pest risk analysis (PRA) has to be performed. Two applications of Confocal Laser Scanning Microscopy (CLSM) are presented here that allow visualizing subtle body structures of selected thrips: (i) fluorescent eyes and (ii) microtrichia. These innovative approaches support the reliable diagnosis of thrips species based on their specific pattern of eye fluorescence caused by different types of ommatidia (the units of a compound eye). A potential species-specific emission pattern provides a useful aid when screening samples prior to detailed morphological analysis. In the best case, the eye fluorescence pattern could be used as an additional diagnostic feature. Only size and number of pigmented ommatidia have yet been considered in existing identification keys. Since a sample is scanned with a laser beam in the CLS microscope, light scattering is minimal, which in turn means that small morphological structures such as microtrichia can be imaged much more accurately. Thus, both CLSM approaches could contribute significantly to facilitating the challenging morphological diagnosis of the tiny thrips.